Diversifikasi Produk Olahan Jagung Manis Sebagai Upaya Peningkatan Nilai Tambah Bagi Petani Jagung di Daerah Wisata Pasir Panjang-Singkawang - Maherawati, Maherawati; Sarbino, Sarbino (Universitas Tanjungpura, 2018)
Pasir Panjang Beach Singkawang is a famous tourist area in West Kalimantan and is one of the corn crops center in Singkawang city. Sweet corn bought as souvenir in the form of fresh vegetables or processed simply into roasted/boiled corn. Corn has not been utilized optimally for various types of food products. To increase the added value of sweet corn for farmers carried out by diversifying corn processing into ice cream, yogurt, and pudding. This activity partner is 35 people member of PKK Group RT 02/06 Kelurahan Sedau, Kecamatan South Singkawang, Singkawang City and Lirang I Farmer Group of Singkawang City. Introduction of technology was done by giving corn processing lectures and the practice of making ice cream, yogurt, and corn pudding. This community service activities can increase the partner's knowledge on corn processing diversification and give the value added of corn. This activity has potensially increased the economic value of corn that will affect the welfare of the community.